Tinjauan Hukum Islam Mengenai Pengobatan Menggunakan Metode Terapi Musik - Muhamad Saddam Nurdin; Irwan Fitri Aco; Rifqi Riswandha Idrus (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to find out and understand one of the health treatment methods that exist in the world of health, and this treatment method is music therapy. This research uses a type of qualitative descriptive research, namely an effort to reveal facts with the aim of accurately describing an existing situation or symptom, using a normative juridical approach method. The research results found are as follows: first, therapy using music media has many benefits for patient health, especially in helping and caring for patient health in addition to main treatment. Second, there are differences of opinion among Islamic scholars regarding the Islamic view of punishing music. However, the majority of Ulama forbid music based on the evidence originating from the Al-Quran, the hadith of the Prophet PBUH. and ijma̕ from four sect imams. Third, seeing that music is haram from the perspective of Islamic law, the use of music as a therapeutic method is haram based on the arguments in the Al-Qur'an, the Hadith of the Prophet SAW. and ijma` four sect imams. And there are also several reasons that support its haraam, such as the level of maṣlaḥatan, and the existence of treatment options that can be used to replace music therapy. It is hoped that the implications of this research will become a reference, literature or consideration for the academic world, as well as positive reference material and information for the government, health workers and society in general.